2021
DOI: 10.1149/1945-7111/ac1892
|View full text |Cite
|
Sign up to set email alerts
|

Methods—Understanding Porous Electrode Impedance and the Implications for the Impedance Analysis of Li-Ion Battery Electrodes

Abstract: Two of the main factors influencing the performance of Li-ion battery (LIB) electrodes are the kinetic losses due to the charge transfer resistance of the active material ( R ct ) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…Therefore, the calculation results and practical example indicate that R ct > R ion /3, which indicates at least the condition of unlimited ion transport, should be satisfied for a power capable electrode design in any energy conversion and storage devices involving charge-transfer reactions. This investigation using the staircase model is not only in good agreement with previous reports, 27 but also provides a detailed boundary for the separation of resistive components that reflects the rate-limiting step changes in the electrochemical process at porous electrodes.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, the calculation results and practical example indicate that R ct > R ion /3, which indicates at least the condition of unlimited ion transport, should be satisfied for a power capable electrode design in any energy conversion and storage devices involving charge-transfer reactions. This investigation using the staircase model is not only in good agreement with previous reports, 27 but also provides a detailed boundary for the separation of resistive components that reflects the rate-limiting step changes in the electrochemical process at porous electrodes.…”
Section: Resultssupporting
confidence: 89%
“…6,25 In contrast, when R ion is sufficiently larger than R ct , Z re,f converging to zero shows the following relationship, which is ion transport limited. 26,27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we carried out simulations of TLM impedance spectra and compared these spectra to the experimental spectra. We found that for improving the agreement between experimental spectra and simulated TLM spectra, two modifications of the TLM were necessary: In eq , the double layer admittance iωC DL had to be replaced by a constant phase element (CPE) expression ( iω ) β Q DL with β < 1, resulting in Such a nonideal capacitive behavior of double layers in composite electrodes has been reported in the literature. , In eq , the factor a v l SE describes the CAM | SE interfacial area normalized by the nominal area of the cathode. However, the appearance of the ionic tortuosity in the factor a v l SE = a v τ Li + d is caused by mapping the 3D morphology of the composite electrode on 1D pores with tortuosities >1.…”
Section: Resultsmentioning
confidence: 99%
“…In a number of studies on lithium-ion batteries, TLMs have been used for analyzing the impedance of composite electrodes with pores filled by the liquid electrolyte. , In this way, charge transfer resistances R CT have been determined and used to calculate exchange current densities j 0 of Li + at the active material | electrolyte interface. Morasch et al examined graphite anodes with variable thickness and determined charge transfer resistances. These charge transfer resistances correspond to exchange current densities in the range 1–6 A m –2 .…”
Section: Introductionmentioning
confidence: 99%